Strategi Partai Demokrasi Indonesia Perjuangan Dalam Mewujudkan Keterwakilan Perempuan di DPRD Kota Tangerang Periode 2019-2024 - Rendy Prihasta (Epistemik Press, 2020)
Law Number 7 article 245 of 2017 concerning general elections regulates a minimum quota of 30% for women candidates in order to increase the number of women's representation in the legislature and serve as a legal requirement for political parties to participate in general elections. The DPC PDI-P Tangerang City and its female legislative candidates take advantage of this affirmative action through a form of political strategy. In this study, the author uses Peter Schroder's theory of political strategy and Rosemarie Putnam Tong’s theory of liberal feminism, using qualitative research methods and through a case study approach. The results of this study conclude that the political strategy carried out by the PDI-P and its legislative candidates in the 2019 election uses an offensive strategy and a defensive strategy. The offensive strategy was carried out by taking an emotional approach to new voters during the campaign period, besides that before the campaign period there was also the role of PDI-P through training and coaching for female cadres and female legislative candidates to be better prepared when serving in internal parties and contesting in the political arena which is general elections. A defensive strategy was also carried out by PDI-P as a government party and by female legislative candidates who had previously experienced victory. The method used in this defensive strategy is to treat old voters and seasonal voters so that they are willing to give their support again.